ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE PROCESS COSTING DAN JOB ORDER COSTING PADA UMKM BAKOEL MINUMAN DI MENDALO - velisha andani; Juwita Rizka; Husnil Fajri; Mellyaembun baining (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Micro, Small, and Medium Enterprises (UMKM) play an important role in the development of Indonesia's economy. One crucial aspect in managing UMKM is the accurate calculation of the cost of goods manufactured (COGM). This study aims to analyze the application of Process Costing and Job Order Costing methods at UMKM Bakoel Minuman in Mendalo. The research method used is descriptive with a case study approach, conducted through direct interviews with the business owner. The results show that UMKM Bakoel Minuman applies the Process Costing method for daily beverage production and the Job Order Costing method for special bulk orders. The implementation of both methods helps the business owner determine more accurate selling prices and improve efficiency in managing production costs.